TOKOH WANITA DAN NILAI MORAL DALAM NOVEL DISGUISED (SANG PENYAMAR): MEMOAR MASA PERANG KARYA RITA LA FONTAINE DE CLERCQ ZUBLI - Asropah, Asropah; Listyarini, Ikha (SASINDO, 2013)
Prominent Women and Moral Value in Disguised Novel (TheDisillusionment): Wartime Memoirs of work Rita La Fontaine De Clercq Zubli ".Semarang: Education Studies Program Language and Literature IKIP PGRISemarang Indonesia. Problem in this research is how the female character andmoral values in Disguised novel (the Disillusionment): Wartime Memoirs of thework of Rita La Fontaine De Clercq Zubli. the purpose of this study was to describethe female character and moral values in the novel Disguised (theDisillusionment): Wartime Memoirs of the work of Rita La Fontaine De ClercqZubli. Methods used in this research is to use the method of analysis, methods ofliterature, and moral approach. Based on data analysis, conclusions can be derivedfrom this study as follows: Disguised novel (the Disillusionment): WartimeMemoirs of the work of Rita La Fontaine De Clercq Zubli contains many moralvalues of seven moral personality. the main character in this novel there is a femalecharacter who is also the author of the novel Disguised (the Disillusionment):Wartime Memoirs, namely Rita La Fontaine De Clercq Zubli. morality heroine canbe found in the events that occurred, such as honesty, authentic values, willingnessto take responsibility, moral courage, moral independence, humility, as well asrealistic and critical.Keywords: female character, moral values, novel.